Pelatihan Pemanfaatan Social Media Tiktok Dalam Peningkatan Pendapatan UMKM Daivik Cell Menggunakan Aplikasi Bangbeli - Renanda Auresty Faradita; Maharani Ikaningtyas (Universitas Muhammadiyah Manado, 2023)
Credit and internet quota have now become the main needs of the community for smartphone users to communicate. As a form of community service, East Java